Cumulative effects of wildfires on forest dynamics in the eastern Cascade Mountains, USA. Issue 2 (19th January 2018) - Reilly, Matthew J.; Elia, Mario; Spies, Thomas A.; Gregory, Matthew J.; Sanesi, Giovanni; Lafortezza, Raffaele
Abstract: Wildfires pose a unique challenge to conservation in fire‐prone regions, yet few studies quantify the cumulative effects of wildfires on forest dynamics (i.e., changes in structural conditions) across landscape and regional scales. We assessed the contribution of wildfire to forest dynamics in the eastern Cascade Mountains, USA from 1985 to 2010 using imputed maps of forest structure (i.e., tree size and canopy cover) and remotely sensed burn severity maps. We addressed three questions: (1) How do dynamics differ between the region as a whole and the unburned portion of the region? (2) How do dynamics vary among vegetation zones differing in biophysical setting and historical fire frequency? (3) How have forest structural conditions changed in a network of late successional reserves (LSRs)? Wildfires affected 10% of forests in the region, but the cumulative effects at this scale were primarily slight losses of closed‐canopy conditions and slight gains in open‐canopy conditions. In the unburned portion of the region (the remaining 90%), closed‐canopy conditions primarily increased despite other concurrent disturbances (e.g., harvest, insects). Although the effects of fire were largely dampened at the regional scale, landscape scale dynamics were far more variable. The warm ponderosa pine and cool mixed conifer zones experienced less fire than the region as a whole despite experiencing the most frequent fire historically. Open‐canopy conditions increased slightly in the mixed conifer zone, but declined across the ponderosa pine zone even with wildfires. Wildfires burned 30% of the cold subalpine zone, which experienced the greatest increase in open‐canopy conditions and losses of closed‐canopy conditions. LSRs were more prone to wildfire than the region as a whole, and experienced slight declines in late seral conditions. Despite losses of late seral conditions, wildfires contributed to some conservation objectives by creating open habitats (e.g., sparse early seral and woodland conditions) that otherwise generally decreased in unburned landscapes despite management efforts to increase landscape diversity. This study demonstrates the potential for wildfires to contribute to regional scale conservation objectives, but implications for management and biodiversity at landscape scales vary geographically among biophysical settings, and are contingent upon historical dynamics and individual species habitat preferences.